Study on the use of rectangular and triangular models in hydroponics for the culture of Anubias barteri var “Broad Leaf” - Cotchakaew, N.; Nuntagij, I.; Laohavisuti, N. (International Journal of Agricultural Technology, 2015)
Hydroponics is a method of culturing plants without the use of soil. Anubias barteri var “Broad Leaf” is an aquatic plant being cultured as a decorative plant in aquaria. It is in demand and is expensive. This research was conducted to compare the use of rectangular and triangular models for the culture of Anubias barteri var “Broad Leaf”. Specifically, to compare the leaf width, leaf length, leaf thickness, number of leaves per plant, chlorophyll content and fresh weight at 120 days after planting. Results revealed that no significant difference was observed among plants in terms of all the parameters studied within each model except for number of leaves per plant in the triangular model. In comparing the two models, no significant difference was observed in all parameters except for plant height wherein plants grown in triangular model were taller than plants grown in the rectangular model.